Perancangan Desain User Interface (UI) Website Nava Rent Car - Bima Aflaha Ahsa; Dwi Mutia Sari (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Nava Rent Car is a car rental service business located in Batam. Many customers have complained about the difficulty in making reservations and obtaining detailed information about the vehicles and services offered. To address this issue, the author designed a more informative, functional, and appealing User Interface (UI) website to support the marketing of services. This design was developed using the Design Thinking method with SWOT analysis techniques. This approach was chosen because it focuses on the user, helping to deeply understand their needs, desires, and problems. The Design Thinking process consists of five steps: empathizing to understand the user's problems, defining the problem, ideating solutions, prototyping, and testing the design for user feedback. The result is a high-fidelity website prototype that illustrates the user flow and measures how well the design meets user needs and provides an optimal experience. Feasibility testing showed positive responses, especially regarding the interface design, clarity of vehicle information, and available features. It is expected that this design will help Nava Rent Car enhance its marketing strategy and expand its business reach.